Functional outcome of anterior bridge plating: a new approach for treating mid shaft humerus fractures - Laha, Sarthak; Gupta, Mainak; Hazra, Rishov (International Journal of Research in Medical Sciences, 2024)
Background: The humerus can be considered the most versatile bone in the human body. Plating can be performed using a classic open approach or minimally invasive methods. Anterior bridge plating with minimally invasive technique in shaft humerus fractures is reported as an acceptable less traumatic and reproducible procedure by several authors. The present study was undertaken to evaluate the efficacy of anterior bridge plating. Methods: The study was carried out involving 35 patients who met the selection criteria and were operated at the tertiary care centre. A 4.5 mm Locking Narrow DCP (Dynamic Compression Plate) was used to fix these fractures. The assessment of the patients was done based on functional and radiological outcomes periodically. Four patients were lost to follow-up, so the final assessment was done based on 31 cases. Results: Of the 31 patients in the study, 23 were males and 8 were females. Twenty three of the thirty-one patients (74.1%) had a history of road traffic accidents. The mean radiological fracture union time was 13.2 weeks (range: 10-16 weeks). Shoulder function was excellent in 26 cases (83.8%) and Elbow function was excellent in 28 cases (90.3%). Conclusions: Mid shaft humerus fractures can be effectively treated with anterior bridge plating with advantages of shorter fracture union time, smaller scars and lower incidence of iatrogenic radial nerve palsies. It also gave better Functional outcome with good patient satisfaction.